Academic Timing and the Relative Age Effect Among Male and Female Athletes in Canadian Interuniversity Volleyball. Issue 1 (February 2020) - Safranyos, Sabrina; Chittle, Laura; Horton, Sean; Dixon, Jess C.
This study examined the moderating effects of academic timing on the relative age effect in men's and women's U Sports (formerly Canadian Interuniversity Sports) volleyball. Interuniversity sport exists within an academic setting and encompasses different age groups within a single team, making it necessary to account for the academic timing of student athletes when studying the relative age effect. To be considered "on-time, " a student athlete's birthdate and expected athletic eligibility status must coincide, while a "delayed" student athlete will have an athletic eligibility corresponding with a younger cohort. We collected birthdates and eligibility years from the U Sports eligibility certificates of 2, 780 male and 3, 715 female athletes for the years 2006–2007 through 2013–2014; we then classified athletes as either on-time or delayed. We used a chi-square (χ 2 ) goodness-of-fit tests to compare the observed distributions of student athletes' actual versus "expected" births across each quartile. Our analyses demonstrated an advantage for athletes born in the first half of the selection year. These results suggest that delaying entry into university may help equalize the playing field for relatively younger athletes wishing to compete in U Sports volleyball.